2018
DOI: 10.14495/jsiaml.10.73
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and practical experiments for maximally stiff structure based on the topology optimization theory and the FEM

Abstract: In this study, numerical studies for a maximally stiff structure based on the topology optimization theory and the FEM are carried out, and the result of several practical tensile tests for the optimized structure was shown. The specimens for tensile testing were made using 3D printer. The numerical studies included filtering radius based examination. The thickness of the optimized model was also investigated, assuming the displacement of the optimized model to be the same as that of the initial model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…The performance function J is a performance index that weights the performance function J 1 to achieve minimal strain energy as shown in Eq. ( 2) (Bendsøe and Sigmund, 2004;Yoshihara et al, 2018) and the performance function J 2 to achieve minimal von Mises stress as shown in Eq. (3) (Le et al, 2010;Zhang and Zhu, 2018).…”
Section: Topology Optimization For Multi-objective Optimization Problemsmentioning
confidence: 99%
“…The performance function J is a performance index that weights the performance function J 1 to achieve minimal strain energy as shown in Eq. ( 2) (Bendsøe and Sigmund, 2004;Yoshihara et al, 2018) and the performance function J 2 to achieve minimal von Mises stress as shown in Eq. (3) (Le et al, 2010;Zhang and Zhu, 2018).…”
Section: Topology Optimization For Multi-objective Optimization Problemsmentioning
confidence: 99%